Socio-demographic and clinical characteristics of the appendicitis patients - Shamsuzzaman; Sikder, Md Alamgir Hossain; Ahmed, Quazi Sabran Uddin; Karim, Md Rezaul; Banik, Shyamol Chandra (Journal of Dhaka National Medical College & Hospital, 2019)
Objective: The aim of the present study was to investigate the Socio-demographic and clinical characteristics of the appendicitis patients at a tertiary level teaching hospital in Dhaka. Methods: It was cross sectional study, conducted in the Dhaka National Medical College Hospital, Dhaka, during the study period of July 2015 to December 2015. The study was approved by the institutional ethical committee. Results: Most of the appendicitis patients belonged to the between 21-30 years which was 64 (32%). Male appendicitis patients (52%) are more than the female patients (48%). Most of the patients were non-smoker (79%). The common symptoms of the patients other than pain were nausea and vomiting (62%). Majority of the patients (56%) duration of symptoms was > 48 hours. Majority of the patients (69%) complains pain occurs in the Right iliac fossa. The nature of the pain was dull aching 54% and 46% were colicky. Conclusion: In our study most of the appendicitis patients belonged to the younger age group. Male patients are more than the female patients. Most of the patients hospitalized with the typical feature of appendicitis like pain in the right iliac fossa with nausea and vomiting. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 48-50